The FORMULASI MINUMAN SERBUK INSTAN DARI CAMPURAN BUAH DAN SAYUR - Husnani Husnani; Tesya Widia Ningsih (Akademi Farmasi Yarsi Pontianak, 2023)
Instant powder drinks are drinks made from fresh or dry ingredients that are boiled for less than 60 minutes, then added sugar or without sugar and the water is evaporated until sugar crystals or powder are obtained. Fruits and vegetables have many health benefits. This study aims to determine the best formula in terms of the physical quality of the preparation of instant powder drink with a mixture of fruits and vegetables. This research was conducted experimentally using variations in the addition of granulated sugar for each formula. Parameters observed included yield, soluble time, pH, water content and organoleptic tests which included color, aroma and taste. Physical stability test of instant powder was carried out at room temperature for one month, namely on days 0, 7, 14, 21 and 28 days. The results showed that formula 2 was the best formula with a water content value of 2%, pH 6, had a dissolving time of less than 5 minutes and was the most preferred formula by respondents.